Mach–Zehnder interferometers incorporating electrochromic molecules for controlled single-photon detection - Scotognella, Francesco (Frontiers in Photonics, 2026)
One particularly fruitful research in the fields of integrated photonics, carried out by a good number of physicists and engineers, concerns the study of different types of materials to be used to control the detection of photons, if not just single photons, in interferometers. In a Mach–Zehnder interferometer, which consists of two beam-splitters, two mirrors, and two detectors, a material that can cause a controlled change in the phase of light in one of the two arms of the interferometer consequently allows control of the probability of detection at the two detectors. In this work, we use an electrochromic molecule, N,N′-bis(cysteine)pyromellitic diimide (BCPD), that has a refractive index dependent on the applied electric field. We simulate the single-photon detection probability in a Mach–Zehnder interferometer with direct light transmission and a waveguide-based Mach–Zehnder interferometer, consisting of two 3-dB couplers connected by two optical channel waveguides. With the employment of the non-equilibrium Green’s function formalism, we have simulated the conductance of BCPD. The results could be of interest in quantum communication.